Investigating the connection between age progression and erectile dysfunction incidence in chronic kidney disease patients undergoing hemodialysis - Widiaputro, Dandi; Suwito, Heru; Eldatarina, Helsa; Firmansah, Wahyu; Akbar, Muhamad; Wattimury, Rosmince; Rahardja, Ketut; Haryanto, Dheni; Gunawan, Atma (Deka in Medicine, 2024)
BACKGROUND: Erectile dysfunction is frequently observed in patients with chronic kidney disease (CKD), especially in the elderly population. However, studies have presented diverse outcomes on this matter. OBJECTIVES: To assess the correlation between age progression and the prevalence of erectile dysfunction in chronic kidney disease patients receiving hemodialysis. METHODS: The study employed a retrospective design and was conducted at RSUD Dr. Saiful Anwar, Malang, during June-July 2022. Data collection involved retrieving age, the erection hardness score (EHS), and baseline characteristics from medical records. Statistical analysis focused on assessing the correlation between age and erectile dysfunction using linear regression. RESULTS: The study population consisted of 59 patients with erectile dysfunction and 61 patients without erectile dysfunction. The primary findings highlighted a substantial and moderately negative association between age and the EHS score, which serves as a key indicator of erectile function. The results suggested that as individuals aged, there was a noticeable trend towards a decrease in the EHS score, implying a decrease in erectile capacity. CONCLUSION: Our findings emphasize the crucial importance of age as a determining factor in the development of erectile dysfunction.